ANO1 inhibits cardiac fibrosis after myocardial infraction via TGF-β/smad3 pathway - Yao Gao (Nature Portfolio, 2017)
Abstract As a newly identified factor in calcium-activated chloride channel, ANO1 participates in various physiological processes like proliferation and differentiation, and expresses in human cardiac fibroblasts. In this experiment, we investigated the function of ANO1 in cardiac fibrosis after myocardial infraction (MI) with methods of Western blotting, Quantitative real-time PCR (qRT-PCR), metabolic reduction of 3-(4,5-dimethylthiozol-2-yl)-2, 5-diphenyltetrazo-lium bromide (MTT), immunofluorescence and confocal imaging, and Masson’s trichrome staining. The results showed that the expression of ANO1 significantly increased in neonatal rats’ cardiac fibroblasts after hypoxia and in cardiac tissues after MI. After ANO1 over-expression, cardiac fibrosis was reduced in vitro and in vivo. Moreover, the expression of TGF-β and p-smad3 declined after ANO1over-expression in cardiac fiborblasts. In conclusion, ANO1 inhibits cardiac fibrosis after MI via TGF-β/smad3 pathway in rats.